GEODETIC SURFACE STRESS AND STRAIN MONITORING IN THE UST-KAMCHATSK AREA: EARTHQUAKE HAZARD ASSESSMENT - Zharinov N.A.; Demyanchuk Yu.V.; Maguskin M.A. (My University, 1996)
Geodetic measurements have been conducted since the early 1970s to monitor surface deformation for seismic hazard assessment in Kamchatka. This paper is concerned with length measurements carried out at a geodetic network in the Ust-Kamchatsk area during 1987-1994.